Thursday

October 2, 2014

October 2, 2014

Posted by **Mary** on Friday, June 29, 2012 at 2:44pm.

- intermeidate algebra -
**Reiny**, Friday, June 29, 2012 at 5:44pmdouble the first

-6x + 8y = 2

-1 times the 2nd

6x - 6y = 3

add them:

2y = 5

y = 5/2

sub into 1st:

-3x + 4(5/2) = 1

-3x = -9

x=3

**Answer this Question**

**Related Questions**

Algebra - Solving system of linear equations by using the apropiate method name ...

Algebra/Elimination method - Solve using the elimination method. If the system ...

Algebra - Solve by elimination method. 7r-3s=14 3r+7s=64 Could never figure out ...

algebra - solve using the elimination method -2x+3y=5 2x-y=1 x+y=6 x-y=4

algebra - Solve by using the elimination method. 9x-y=72 x+4y=45

algebra - Solve by using the elimination method. 7x-8y=-20 8x+7y=74

algebra - Solve by using the elimination method. 2x=2+4y -3/2x+y=-31/2

algebra - solve using the elimination method x+7y=58 -x+4y=30

Algebra - Solve using the elimination method. 2x +3y = 2, 4x + 6y =4.

math elimination method - elimination method really confuses me. solve by ...